2006
DOI: 10.1021/es060124x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Illite Clay for In Situ Remediation of 137Cs-Contaminated Water Bodies:  Field Demonstration of Reduced Biological Uptake

Abstract: We hypothesized that adding micaceous minerals to 137Cs-contaminated aquatic systems would serve as an effective in situ remediation technique by sequestering the contaminant and reducing its bioavailability. Results from several laboratory studies are presented from which an effective amendment material was chosen for a replicated field study. The field study was conducted over a 2-year period and incorporated 16 3.3-m diameter column-plots (limnocorrals) that were randomly placed in a 137Cs-contaminated pond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
0
13
1
Order By: Relevance
“…In the Fukushima region, in particular, 137 Cs is the main source of external radiation dose five years after the nuclear disaster of March 2011. The most important process controlling the solubility and mobility of cesium in soils, sediments, and sedimentary rocks is the formation of strong surface complexes with clay minerals [1] and particularly with the micaceous minerals, illite, vermiculite, and mica [28,40,11,63,65]. Cesium adsorption on illite is of particular importance in the geologic storage of radioactive waste, because illite often dominates the mineralogy of finegrained sedimentary rocks considered for use as host formations [94,35,17].…”
Section: Introductionmentioning
confidence: 99%
“…In the Fukushima region, in particular, 137 Cs is the main source of external radiation dose five years after the nuclear disaster of March 2011. The most important process controlling the solubility and mobility of cesium in soils, sediments, and sedimentary rocks is the formation of strong surface complexes with clay minerals [1] and particularly with the micaceous minerals, illite, vermiculite, and mica [28,40,11,63,65]. Cesium adsorption on illite is of particular importance in the geologic storage of radioactive waste, because illite often dominates the mineralogy of finegrained sedimentary rocks considered for use as host formations [94,35,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, a component that cannot be ignored that will affect the soils ability to retain 137Cs especially in sandy soils is rainfall. During drought years, 137Cs is much more bioavailable in many soil types (Golmakani et al 2008;Goor et al 2003;Heckman and Kamprath 1992;Hinton et al 2006;Leigh and Johnston 1983;Nimis 1996). This is most likely demonstrated in the variability of the data for nonindustrial impacted compartments throughout the SRS.…”
Section: Discussion and Management Recommendationsmentioning
confidence: 99%
“…Additionally, while the actual uptake of 137 Cs varied between the two plant species, the general trends were similar, demonstrating the effectiveness of this treatment among plant species. A field demonstration study research at SRS demonstrated the potential for 137 Cs concentrations to be reduced in the water column, aquatic plants, and fish by the addition of illite (Hinton et al 2006). This remediation strategy could provide a less environmentally destructive and more cost effective alternative to conventional contaminant removal methods (Hinton et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This will be discussed in more detail below. Previous research at SRS evaluated the ability of different clays to sequester 137 Cs and verified that Todd Light Illite is among the most effective (Hinton et al 2006).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation